Atropisomerism in Styrene: Synthesis, Stability, and Applications - Feng, Jia; Gu, Zhenhua (SynOpen, 2021)
Atropisomeric styrenes are a class of optically active compounds, the chirality of which results from restricted rotation of the C(vinyl)–C(aryl) single bond. In comparison with biaryl atropisomers, the less rigid skeleton of styrenes usually leads them to have lower rotational barriers. Although it has been overlooked for a long time, scientists have paid attention to this class of unique molecules in recent years and have developed many methods for the preparation of optically active atropisomeric styrenes. In this article, we review the development of the concept of atropisomeric styrenes, along with their isolation, asymmetric synthesis, and synthetic applications.1 Introduction2 The Concept of Styrene Atropisomerism3 Early Research: Separation of Optically Active Styrenes4 Synthesis of Optically Active Styrenes5 Stability of the Chirality of Atropisomeric Styrenes6 Outlook
Keywords: atropisomers; styrene; axial chirality; asymmetric synthesis; asymmetric C–H functionalization